Dakwah di Era Algoritma: Dialektika Etika dan Strategi Adaptasi Komunikasi Penyiaran Islam Berbasis Artificial Intelligence - Herman Dermawan (Penerbit Cahaya Kata, 2026)
The presence of Artificial Intelligence (AI) has disrupted the landscape of Islamic broadcasting communication, shifting interaction patterns from physical pulpits to digital spaces controlled by algorithms. This study aims to analyze ethical challenges and formulate adaptation strategies for da'is and Islamic broadcasting practitioners in facing the era of content automation. The method used is qualitative with a library research approach, examining literature, journals, and recent reports regarding AI and da'wah from the 2020-2025 period. The results show that the use of AI in da'wah presents two sides of the same coin: the efficiency of message dissemination (reach) and the degradation of religious authority. The main ethical challenges include algorithmic bias, the potential for deepfakes of clerics, and the loss of the sanctity of talaqqi. The strategy offered is